Analysis of effect of annealing at high temperature on nickel oxide and zinc oxide thin film for solar cell applications - Iskandar Dzulkarnain Rummaja; Nur Afiqah Hani Senin; Muhammad Idzdihar Idris; Zarina Baharudin Zamani; Radi Husin Ramlee; Luke Bradley (Indonesian Journal of Electrical Engineering and Computer Science, 2024)
The use of thin films in solar cell technology has gained substantial interest because of their potential for cost-effective and efficient energy conversion. nickel oxide (NiO) and zinc oxide (ZnO) have been used as potential materials in solar cells application especially third generation solar cells because of their good characteristics, such as high electrical conductivity, chemical stability, resistance to degradation, and abundance and low cost. However, at high temperatures, both NiO and ZnO can undergo thermal decomposition and exhibit crystal defects and grain boundaries. This work investigates high temperature annealing on the morphology, structural, and optical properties of NiO and ZnO thin films. The deposited material was annealed at 500 ℃, 600 ℃, and 700 ℃ and be characterized via scanning electron microscopy (SEM), XRD, and UV-Vi’s spectroscopy. The results showed that inceasing the annealing temperature can improve both ZnO and NiO thin films in structure and appearance. For ZnO, higher temperatures made the grains bigger and more orderly, and for NiO, the process made the grains more organized, bigger in size, and spread out more evenly. However, annealing at high temperature yields a smaller bandgap energy value for both thin films.